The effect of biological agent and botanical fungicides on maize downy mildew - Joko Prasetyo; Cipta Ginting; Hasriadi Mat Akin; Radix Suharjo; Ainin Niswati; Auliana Afandi; Reza Adiwijaya; SUDIONO SUDIONO; MUHAMMAD NURDIN (Society for Indonesian Biodiversity, 2021)
Abstract. Prasetyo J, Ginting C, Akin HM, Suharjo R, Niswati A, Afandi A, Adiwijaya R, Sudiono, Nurdin M. 2021. The effect of biological agent and botanical fungicides on maize downy mildew. Biodiversitas 22: 1652-1657. This study was conducted to evaluate the effect of the combination of Trichoderma asperellum and mycorrhizae with botanical fungicides made from betel leaf extract or turmeric extract against maize downy mildew. The study used a randomized complete block (RCB) design with three replications. The treatments applied were: single applications of T. asperellum (Ta); arbuscular mycorrhizal fungi (AMF); turmeric extract (T); betel extract (B); the combination of T. asperellum and AMF (TaM); turmeric extract and T. asperellum (TTa); turmeric extract and AMF (TM); turmeric extract + T. asperellum + AMF (TTaM); betel extract + T. asperellum (BTa); betel extract + AMF (BM); betel + T. asperellum + AMF (BTaM); and Control (C). The observed variables were disease incidence, incubation period, and shoot dry weight. The data were analyzed using ANOVA. Differences between treatments were tested by the LSD test at 5% significance level. The results showed that the combination of botanical fungicides with biological agents could reduce the incidence of downy mildew, extend the incubation period, and increase the dry weight of corn shoots. The best combination treatment was achieved from the combination of T. asperellum with betel extract. There was a synergistic effect between botanical fungicides and biological agents in reducing the disease incidence.